Soil erodibility parameters for two soils with different soil moisture content evaluated with the mini-Jet Erosion Test (JET) - Akin, Aaron A; Sheshukov, Aleksey Y (Mendeley Data, 2024)
Soil erosion by water leads to various surface water problems including sedimentation of streams and reservoirs, degradation of soil health, reduction of water quality, and other. Soil detachment by water can be described by the excess shear stress equation. Values of two physical soil erodibility parameters, erodibility coefficient and critical shear stress, presented in the non-linear excess shear stress equation can be generated with a laboratory mini-Jet Erosion Test (JET). Raw JET experiment data is scour depth versus time. This dataset contains the results of JET experiments on two studied soils: silty clay loam (soil I, 16% sand, 48% silt, 36% clay, 4.25% organic matter, 1.45 Mg/m3 bulk density) from a tilled row crop field and clay loam (soil II, 38% sand, 32% silt, 30% clay, 4.13% organic matter, 1.49 Mg/m3 bulk density) from an annually grazed pasture. A total of 32 JET experiments (17 for silty clay soil I and 15 for clay soil II) were conducted on the samples with 0 g to 423 g initially infiltrated masses of water. For each JET experiment, the scour depth was recorded as a function of time. The experiment ended when the scour depth did not change after at least two scouring periods, and 30 to 38 periods were needed to reach the equilibrium depth. During the experiments, the time step increased from 15 sec at the beginning to 300 seconds at the end. The final scour depth varied from the smallest of 31 cm for a 0 g water for silty clay loam soil to the deepest of 46 cm for clay soil. The data files in the dataset are organized by the soil type and sorted by the index for the mass of initially infiltrated water provided in the summary file.
Keywords: Hydraulics; Soil Erosion; Agricultural Soil